2017
DOI: 10.1080/0886022x.2017.1358180
|View full text |Cite
|
Sign up to set email alerts
|

The association between methylation levels of targeted genes and albuminuria in patients with early diabetic kidney disease

Abstract: The present study provided evidence that hypomethylation of TIMP-2 and AKR1B1 genes can be associated with albuminuria in patients with early DN. We may speculate that the hypomethylation of TIMP-2 and AKR1B1 genes may be an early surrogate marker of DN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…27 Besides, these methods were also used to predict the risk of drug noncompliance in Chinese patients with inflammatory rheumatism. 2,2 To further verify the stability of this prediction model, the whole data set was used for internal verification, and the C index was obtained. Note: Data are presented as n (%), mean±SD or median (IQR).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…27 Besides, these methods were also used to predict the risk of drug noncompliance in Chinese patients with inflammatory rheumatism. 2,2 To further verify the stability of this prediction model, the whole data set was used for internal verification, and the C index was obtained. Note: Data are presented as n (%), mean±SD or median (IQR).…”
Section: Discussionmentioning
confidence: 99%
“…DN and DR not only impose a heavy financial burden associated with medical treatment but also seriously affect the quality of life of the patients and increases the risk of death of T2DM patients. 2 DN and DR are closely related. Some studies have shown that the prevalence of DR in patients with DN confirmed by biopsy was 48%, 9 and the prevalence of DN in patients with confirmed DR was 35.6%.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies exploring blood-derived DNA methylation used an EWAS approach for DKD focused on the 27K array (Sapienza et al, 2011), the mitochondrial genome (Swan et al, 2015) or renal function decline in 181 Pima Indians with diabetes (Qiu et al, 2018). Targeted DNA methylation studies have been conducted using blood-derived DNA (Aldemir et al, 2017;Smyth et al, 2018), cell models of DKD (Brennan et al, 2010;Li et al, 2019) and an EWAS reported on kidney biopsy samples from 91 individuals of whom 45% had diabetes (Gluck et al, 2019) and 11 individuals with diabetes (Ko et al, 2013). The case and control population employed in this study has >60% power to detect a true positive (defined as detected CpGs with a meaningful difference in mean blood derived DNA methylation ±0.2 with a false discovery rate P ≤ 0.05) association using pwrEWAS (Graw et al, 2019).…”
Section: Discussionmentioning
confidence: 99%